Strategi Meningkatan Kualitas Pendidikan Anak Usia Dini: Studi Komparatif Manajemen RA Dan TK - Baroroh, Fatimatul; Nurrochim, Nurrochim; Waruwu, Nurdelima; Ratnaningsih, Sita; Maftuhah, Maftuhah; Asy’ari, Hasyim (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2024)
Early Childhood Education (ECE) plays a critical role in laying the foundation for children's development, making effective management strategies in educational institutions essential. This study aims to explore the application of core management functions—planning, organizing, implementing, and controlling—to enhance educational quality in Raudhatul Athfal (RA) and Kindergarten / Taman Kanak-Kanak (TK). Conducted at RA Baitul Maal and TK Bintaro, the research adopts a qualitative approach, utilizing in-depth interviews with school leaders and teachers, direct observations, and document analysis to identify similarities and differences in management strategies. The findings reveal that in planning, RA Baitul Maal prioritizes structured and evaluative long-term plans, while TK Bintaro emphasizes curriculum innovation and technology integration. In organizing, RA Baitul Maal demonstrates better adherence to national ECE standards, whereas TK Bintaro shows room for improvement in aligning staff qualifications with assigned roles. Implementation strategies highlight each institution's uniqueness, with RA Baitul Maal excelling in religiously motivated activities and TK Bintaro fostering an innovative organizational culture. Supervision mechanisms in both institutions involve embedded and functional oversight, with differences in external monitoring based on institutional affiliation (Ministry of Religious Affairs for RA and Ministry of Education for TK). These findings underscore the importance of adapting management functions to the distinctive characteristics of each institution. The implications suggest that well-directed management strategies can significantly enhance educational quality and support children's holistic development.